Meeting the Nutrition and Feeding Needs of Children with Disabilities: A Training Model for Health and Education Personnel in the Outer Pacific - Wendy L. Tada; Marion Taylor Baer; Nancy B. Robinson; Henry Ichiho (Journal of Research in Rural Education, 1998)
Infants and children with disabilities are at increased risk for problems with nutrition, feeding, and growth. Such problems are particularly acute in the US. Pacific jurisdictions where the overall health status is poor in comparison to US. national standards. As with many rural areas in the US., the US. Pacific jurisdictions lack adequate numbers of trained personnel to meet the feeding and nutrition needs of children with disabilities and their families. In order to address this need, a "nutrition mentoring" program was developed to train local health and education personnel in the US. Pacific region to provide nutrition andfeeding supports to children with disabilities and their families. This article describes the training model and its implementation, as well as the benefits and challenges of implementing a similar program in rural areas ofthe US.